Impact of porcine circovirus type 2 on porcine epidemic diarrhea virus replication in the IPI-FX cell line depends on the order of infection - Zhang, Hao; Shi, Hongyan; Wei, Yanwu; Shi, Da; Cao, Mengxiang; Liu, Jianbo; Liu, Jianhang; Li, Liang; Liu, Changming; Feng, Li; Huang, Liping (Frontiers in Microbiology, 2023)
A study in 2006 showed that 21-day transplacental Porcine circovirus type 2 (PCV2) infections aggravate the small-intestinal pathological damage caused by Porcine epidemic diarrhea virus (PEDV) infection in piglets. Therefore, we investigated whether the small intestine supports PCV2 replication and the effect of PCV2 infection on PEDV replication in epithelial cells in vitro. To confirm the intestinal tropism of PCV2, the viral loads in the small-intestinal tissues after PCV2 infection were determined with viral titration, and the viral titers in the infected pig jejunum, ileum, ileocecal valve, and colon were 104.86, 104.09, 102.52, and 102.35 TCID50/g, respectively. We then determined the propagation characteristics of PCV2 in ileal epithelial cells (IPI-FX) and jejunal epithelial cells (IPEC-J2) with an immunoperoxidase monolayer assay, viral titration, and an immunofluorescence assay. Both IPI-FX and IPEC-J2 cells supported the replication of PCV2, with titers of 105.5 and 105.0 TCID50/ml, respectively. We established an infection model of PCV2 and PEDV in IPI-FX cells and found that PEDV and PCV2 infected the cells individually and together. The effects of PCV2 infection on PEDV replication were determined with reverse transcription–quantitative PCR (qPCR), western blotting, and viral titration. When PCV2 infected IPI-FX cells before PEDV, PCV2 significantly inhibited the replication of PEDV in a dose- and time-dependent manner and that the mRNAs of IFN-β, TNF-α, IL1β, and OASL were downregulated (detected with qPCR). Surprisingly, when IPI-FX cells were co-infected with PCV2 and PEDV, PCV2 promoted the replication of PEDV, the expression of the host IFN-β, TNF-α, IL1β, and OASL mRNAs was upregulated. These findings demonstrate that the co-infection of IPI-FX cells with PCV2 and PEDV represents an excellent in vitro model in which to investigate their combined pathogenic mechanisms.